THE Tyrannosaurus SKULL FROM THE “JOSÉ NARCISO ROVIROSA ANDRADE” MUSEUM OF NATURAL HISTORY, TABASCO: PART ONE - Jiménez Contreras, Alfredo Abraham; García Rovirosa, Yajaira (Kuxulkab', 2025)
In 1984, the "José Narciso Rovirosa Andrade" Museum of Natural History was founded, which exhibits the history of evolution; The dinosaur section is the most prominent and favorite of its visitors. Among its most important pieces is a replica of the skull of "Tyrannosaurus rex", and although unknown to the public as to its origin, it has great tourist and cultural relevance. This exhibition, which is presumed to be part of the famous specimen "AMNH 5027" that is exhibited at the American Museum of Natural History in New York, is significant for being the first assembly of "T. rex", made by Henry Fairfield Osborn who described the specimen in 1916, its cultural and social impact is remarkable.
Keywords: Anatomy; Curation; Dinosaur; Skeleton; Villahermosa